VISION TOWARD MANAGERIAL PERFORMANCE AT UIN AR-RANIRY BANDA ACEH - Aulia Kesuma, Hasan Basri, Heru Fahlevi. (Universitas Syiah Kuala, 2016)
Abstract: This study aimed to examine the influence of budget participation, goal clarity and budget revision toward managerial performance simultaneously and partiallyat UIN Ar-Raniry Banda Aceh. This study is hypothesis testing research by testing using multiple linear regression of the data collected through questionnaires. The study population uses 59 employees who responsible for planning and budgeting at UIN Ar-Raniry Banda Aceh. Data analysis was performed using SPSS (Statistical Package for Social Science) version 20. The results showed that budget participation, goal clarity and budget revision, either simultaneously or partially influence managerial performance at UIN Ar-Raniry Banda Aceh.Keywords: Budget Participation, Goal Clarity, Budget Revision, and Managerial Performance. Abstrak: Penelitian ini bertujuan untuk menguji pengaruh partisipasi penyusunan anggaran, kejelasan sasaran dan revisi anggaran secara bersama-sama maupun parsial terhadap kinerja manajerial pada UIN Ar-Raniry Banda Aceh. Penelitian ini merupakan penelitian pengujian hipotesis dengan pengujian menggunakan regresi linier berganda dari data yang dikumpulkan melalui kuesioner. Populasi penelitian menggunakan 59 pejabat penanggungjawab perencanaan dan penganggaran pada UIN Ar-Raniry Banda Aceh. Analisis data dilakukan menggunakan SPSS (Statistical Package for Social Science) versi 20. Hasil penelitian menunjukkan bahwa partisipasi anggaraan, kejelasan sasaran dan revisi anggaran, baik secara simultan maupun parsial berpengaruh terhadap kinerja manajerial pada UIN Ar-Raniry Banda Aceh.Kata kunci: Partisipasi Penyusunan Anggaran, Kejelasan Sasaran, Revisi Anggaran, Kinerja Manajerial.